Evaluasi Implementasi Akad dalam Asuransi Syari'ah di Indoensia: Studi Kasus Wakalah, Al-Wadiah dan Musyarakah - Syamsuddin, Syamsuddin; Abbas, Ngatmin (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This research aims to evaluate the implementation of contracts (akad) in Islamic insurance in Indonesia, identify challenges faced, and propose strategies to enhance effectiveness. The study focuses on Wakalah, Al-Wadiah, and Musyarakah contracts. Employing a qualitative method with a library research approach, this study analyzes various literature sources, regulatory documents, and industry reports. The results indicate that the Wakalah contract is predominantly used, while Al-Wadiah and Musyarakah have more limited implementation. Key challenges identified include lack of standardization, complexity in underwriting surplus calculations, and limited understanding among practitioners and the public. Proposed strategies to improve the effectiveness of contract implementation include enhancing education, developing adaptive regulations, standardizing practices, investing in technology, and product innovation. The research also highlights the importance of strengthening sharia governance and developing digital platforms to increase transparency and efficiency. In conclusion, while the implementation of contracts in Islamic insurance in Indonesia has shown progress, there remains significant room for improvement and innovation to ensure compliance with sharia principles and meet societal needs